PICC line associated blood stream infections: an analysis of host and device factors (Translation: The University of Toledo Journal of Medical Sciences, 2021)
Background: Risk factors for PICC CLABSI (peripherally inserted central venous catheter/ central line associated bloodstream infections) have been evaluated in a limited number of prospective and retrospective studies with conflicting results.Methods: A six year retrospective review of PICC CLABSI within a single institution was performed. PICC CLABSI cases were matched to uninfected controls and host and device data were extracted from comprehensive medical record reviews. A statistical analysis of PICC CLABSI risk factors compared to matched controls was performed.Results: 6756 patients had a PICC line placed during the study period (January 1, 2008 - December 31, 2013). Fifty-six (0.83%) CLABSI were identified and matched to 245 uninfected controls. Factors associated with PICC CLABSI included: sepsis (P
Keywords: PICC line; bloodstream infection